2020
DOI: 10.36227/techrxiv.12535010.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey on Deep Transfer Learning and Edge Computing for Mitigating the COVID-19

Abstract: This article has no data to published separately. All descriptions are mentioned in the article. This is a systematic review and discussion with possible solutions with deep transfer learning over the edge computing model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The various security mechanisms are employed in sending and receiving data from these smart applications [ 12 ]. Smartphones can be used as input devices such as sensing, storing, and computing the results [ 13 ]. By the use of technology, it is possible to detect the COVID-19 suspects in early stages to eliminate the spread of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The various security mechanisms are employed in sending and receiving data from these smart applications [ 12 ]. Smartphones can be used as input devices such as sensing, storing, and computing the results [ 13 ]. By the use of technology, it is possible to detect the COVID-19 suspects in early stages to eliminate the spread of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to extract such features from non-medical images can be "transferred" to a medical image classification application, known as transfer learning [4]. The 3 pretrained CNNs used were ResNet50, VGG19 and VGG16, each of which were prepared in Python using Tensorflow and Keras [19].…”
Section: Convolutional Neural Network (Cnns)mentioning
confidence: 99%
“…It is not exclusively required to develop a custom CNN to perform medical image diagnoses, however. Instead, a process known as transfer learning can be used, in which the feature extraction ability learned by a CNN trained on a different dataset can be transferred to assist in classifying images from a different application [4]. Zouch et al (2022) employed a CNN transfer learning approach, comparing the performance of the ResNet50 and VGG19 CNNs pretrained on the ImageNet dataset [5].…”
Section: Introductionmentioning
confidence: 99%
“…Next, [18] they optimized the transfer learning model by using twofold learning to improve accuracy in classifying chest X-rays on labels: COVID-19, viral pneumonia, and normal. The proposed model reportedly achieves 99.4% accuracy with an F1 score (0.994), in work [19] proposes a new anti-noise framework for the learning of noisy labels for segmentation tasks then proposes a new COVID-19 Pneumonia Lesions segmentation network (COPLE) -Net) to better deal with lesions of various scales and appearances, to make the training process noisy label resilient, they propose a noise-resistant Dice loss function and integrate it into a standalone ensemble framework and the result of this method is the noise function robust loss, and COPLE Net achieved higher performance than the advanced CNN for medical image segmentation, and work [20] reported that chest CT scan images were an effective screening strategy because they could reveal some cases of COVID-19 so it could be applied to shows symptoms in the early stages and pulmonary consolidation in the late stages.…”
Section: Introductionmentioning
confidence: 99%